If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2t + 4) = 0 Reorder the terms: -2(4 + 2t) = 0 (4 * -2 + 2t * -2) = 0 (-8 + -4t) = 0 Solving -8 + -4t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -4t = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -4t = 0 + 8 -4t = 0 + 8 Combine like terms: 0 + 8 = 8 -4t = 8 Divide each side by '-4'. t = -2 Simplifying t = -2
| 8=13-3y-4 | | 11-y=0 | | 3x-4=(x-4) | | 12-y=-6 | | r+0.5r=1650 | | X^2-xk+3x-4=0 | | c+3c+2=5c-1 | | x+0.25x=43 | | 2x-3=5x-3x-3x | | 22.8-9p=8p+2.4 | | 4(2m-5)=28 | | 38700+x-.01x-223939=50000 | | 9k+4.2=k+8 | | -9y+4y-2= | | F-8=-3f | | z-14=-1 | | 22.4-9p=8p+2.4 | | 5x^3+6x^2+3x+14=x+1 | | -3b+2=4b-12 | | z+8=25 | | z+11=28 | | 3x+9-2x= | | 5x+12-4x+3=12 | | 3x-1=6x-4 | | 2^7/6-14=0 | | z+18=28 | | 1000.00/.35 | | x+x+.7x=1 | | 2sec^2t-4=0 | | 3-2(2x-3)+3(1-2x)=8 | | 100.00/.35 | | X+x+.7x= |